The Role of Dakwah On The Development Of Islamic Education In Sosor Ladang Village Toba Samosir District - Hotni Sari Harahap; Muhammad Riduan Harahap (Sean Institute, 2021)
This study describes the role of da'wah on the development of Islamic education in the Muslim Minority Village, namely Sosor Field Village, Toba Samosir Regency. This study uses a qualitative approach with a descriptive type of research. Based on the results of the study, it can be concluded that: The role of da'wah in developing Islamic education in Sosor Ladang village plays a role as educators and Da'i in broadcasting Islamic teachings and civilization in Minority villages with programs of routine recitation activities, celebration of Islamic Religious Holidays, managing institutions non-formal education, carrying out tabligh Akbar, forming associations such as perwiridan/recitation of fathers, mothers, and teenagers, also forming a Qur'an education park as a form of fostering the Qur'anic generation.